Vindoline Inhibits RANKL-Induced Osteoclastogenesis and Prevents Ovariectomy-Induced Bone Loss in Mice - Zhan, Yunfei; Liang, Jiamin; Tian, Kun; Che, Zhigang; Wang, Ziyi; Yang, Xue; Su, Yuangang; Lin, Xixi; Song, Fangming; Zhao, Jinmin; Xu, Jiake; Liu, Qian; et al. (Frontiers in Pharmacology, 2020)
Osteolytic bone diseases, for example postmenopausal osteoporosis, arise from the imbalances between osteoclasts and osteoblasts in the bone remodeling process, whereby osteoclastic bone resorption greatly exceeds osteoblastic bone formation resulting in severe bone loss and deterioration in bone structure and microarchitecture. Therefore, the identification of agents that can inhibit osteoclast formation and/or function for the treatment of osteolytic bone disease has been the focus of bone and orthopedic research. Vindoline (Vin), an indole alkaloid extracted from the medicinal plant Catharanthus roseus, has been shown to possess extensive biological and pharmacological benefits, but its effects on bone metabolism remains to be documented. Our study demonstrated for the first time, that Vin could inhibit osteoclast differentiation from bone marrow macrophages (BMMs) precursor cells as well as mature osteoclastic bone resorption. We further determined that the underlying molecular mechanism of action of Vin is in part due to its inhibitory effect against the activation of MAPK including p38, JNK, and ERK and intracellular reactive oxygen species (ROS) production. This effect ultimately suppressed the induction of c-Fos and NFATc1, which consequently downregulated the expression of the genes required for osteoclast formation and bone resorption. Consistent with our in vitro findings, in vivo administration of Vin protected mice against ovariectomy (OVX)-induced bone loss and trabecular bone deterioration. These results provided promising evidence for the potential therapeutic application of Vin as a novel treatment option against osteolytic diseases.